Kajian Hidrolika Bangunan Pelimpah Samping (Side Channel Spillway) Bendungan Pomalaa Kabupaten Kolaka Provinsi Sulawesi Tenggara Dengan Uji Model Fisik 1:40 - Paksi, R. Susenatama Jatayu; Dermawan, Very; Andawayanti, Ussy (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
Pomalaa Dam designed to settle nickel mining wasted material ran by PT. Vale Indonesia, a physical model test is required to accomplish the design. This study aimed to determine the comparison of Pomalaa Dam side-channel spillway hydraulic condition between physical model test and theoretical analysis. In the analysis of the water level profile, debits of Q100th, Q1000th, and QPMF were examined. Spillway hydraulic analyzed by continuity equation with Cd calculation using the Iwasaki method. The water level in the transition channel and chute way calculated by the energy equation with the standard stage method. The side ditch and stilling basin hydraulic analyzed by momentum equations law. The vibration flow risk and cavitation respectively analyzed using Vendernikov-Montuori numbers and dimensionless parameters. The results of the hydraulic model test show that in the original design there is a non-uniform flow in the transition channel, the piezometer shows negative pressure in the chute channels section 2 and 3, but still safe. But the cavitation calculation using water velocity (v) and water depth (h) shows that cavitation occurred in the chute channels section 2 and 3 at the Q100th and Q1000th discharge and supercritical flow occurred at the end channel after the energy dissipator.